Evaluation of hygienic condition of Chinese electronic fly catcher trap bait using microbiological approach - Saiful Bahri, Mohamed; M. S., Hamid; N. I. A. M., Daud; N. M., Mohamad (2017)
Survival of pathogenic bacteria is usually popular topic in food studies. Thus, applying this technique to identify the hygienic condition of house flies’ bait is required in order to minimize outbreaks of bait illnesses. Hence, the main objective of this paper is to study the hygienic condition of Chinese Electronic Fly Catcher Trap (CEFCT) bait which has already been proven as an effective bait for attracting flies in Malaysia. Therefore, the hygienic condition of CEFCT bait was evaluated by using the spread plate method under selective media such as de Man, Rogosa and Sharpe (MRS) agar, Eosin Methylene Blue (EMB) agar and Dichloran Rose Bengal Chlortetract Cycline (DRBC) agar. All these agars were used to identify the number of hazardous bacteria that can survive under these test conditions. A colony-forming unit (CFU) per ml was used in the experiment to estimate the number of viable plate count within the range of 1.39 to 1.56 in logarithmic scale. Eventually, experimental results show that no significant growth of E. coli, Lactobacilus yeasts and moulds were formed in four days’ incubation period at 37oC. This indicates that the CEFCT bait is hygienic and can be used safely for attracting house fly without threatening wildlife and humans.